Evaluation of treatment response to autologous transplantation of noncultured melanocyte/keratinocyte cell suspension in patients with stable vitiligo - Mariana Gontijo Ramos; Daniel Gontijo Ramos; Camila Gontijo Ramos (Sociedade Brasileira de Dermatologia, 2017)
Abstract Background: Vitiligo is a chronic disease characterized by the appearance of achromic macules caused by melanocyte destruction. Surgical treatments with melanocyte transplantation can be used for stable vitiligo cases. Objectives: To evaluate treatment response to the autologous transplantation of noncultured epidermal cell suspension in patients with stable vitiligo. Methods: Case series study in patients with stable vitiligo submitted to noncultured epidermal cell suspension transplantation and evaluated at least once, between 3 and 6 months after the procedure, to observe repigmentation and possible adverse effects. The maximum follow-up period for some patients was 24 months. Results: Of the 20 patients who underwent 24 procedures, 25% showed an excellent rate of repigmentation, 50% good repigmentation, 15% regular, and 10% poor response. The best results were observed in face and neck lesions, while the worst in extremity lesions (88% and 33% of satisfactory responses, respectively). Patients with segmental vitiligo had a better response (84%) compared to non-segmental ones (63%). As side effects were observed hyperpigmentation of the treated area and the appearance of Koebner phenomenon in the donor area. Study limitations: Some limitations of the study included the small number of patients, a subjective evaluation, and the lack of long-term follow-up on the results. CONCLUSION: Noncultured epidermal cell suspension transplantation is efficient and well tolerated for stable vitiligo treatment, especially for segmental vitiligo on the face and neck.